Diaspora, identity, and religion : new directions in theory and research - Kokot, Waltraud; Tölölyan, Khachig; Alfonso, Carolin, 1969- (Routledge, 2004)
Examines the development of the concept of diaspora and new perspectives on global networks and local identities. Features case histories on the Caribbean, Irish, Irish-American, Armenian, African and Greek diasporas.
Title from PDF title page (viewed 25 Nov., 2009).
Keywords: Emigration and immigration.; Ethnic relations -- Political aspects.; Group identity.; Religious minorities.; Space and time -- Social aspects.; Emigration and Immigration; Social Identification; Émigration et immigration.; Relations interethniques -- Aspect politique.; Identité collective.; Minorités religieuses.; Espace et temps -- Aspect social.; group identity.; SOCIAL SCIENCE -- Emigration & Immigration.; Emigration and immigration; Ethnic relations -- Political aspects; Group identity; Religious minorities; Space and time -- Social aspects; Diaspora.; Identiteit.; Godsdienst.